2017
DOI: 10.1002/chem.201701970
|View full text |Cite
|
Sign up to set email alerts
|

Gold Redox Catalysis through Base‐Initiated Diazonium Decomposition toward Alkene, Alkyne, and Allene Activation

Abstract: The discovery of photo-assisted diazonium activation toward gold(I) oxidation greatly extended the scope of gold redox catalysis by avoiding the use of a strong oxidant. Some practical issues that limit the application of this new type of chemistry are the relative low efficiency (long reaction time and low conversion) and the strict reaction condition control that is necessary (degassing and inert reaction environment). Herein, an alternative photo-free condition has been developed through Lewis base induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 110 publications
0
29
0
1
Order By: Relevance
“…This iodine-catalyzed diazo activation originated from an accidental discovery 17 20 . It has been recently reported that aryl diazonium salts (ArN 2 + ) are effective oxidants in promoting gold(I) oxidation to gold(III) 21 23 . To extend the reactivity to alkyl diazonium salt, we hypothesized that treating diazo compound with proper electrophile could generate a reactive diazonium intermediate in situ, which might serve as a potential oxidant for gold(I) oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…This iodine-catalyzed diazo activation originated from an accidental discovery 17 20 . It has been recently reported that aryl diazonium salts (ArN 2 + ) are effective oxidants in promoting gold(I) oxidation to gold(III) 21 23 . To extend the reactivity to alkyl diazonium salt, we hypothesized that treating diazo compound with proper electrophile could generate a reactive diazonium intermediate in situ, which might serve as a potential oxidant for gold(I) oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…[237] Pivotal to the successo ft he reactions was the use of 2,2'-bipyridine (bpy) ligand and the base Na 2 CO 3 .T he mechanistic studies revealed that Na 2 CO 3 assists the formation of an initial alkynyl or arylgold complex.T his Au complex bonds to the aryl-diazonium salts to produce an Au III intermediate. [238] The base promotes an initial decomposition of the aryl diazonium salt and assists in the subsequento xidation of Au I to Au III .T he poor reactivity observedu nder photochemical conditions confirmed that the reaction occurs preferentially under thermal/chemical activation. However, the mechanisms of bpy-assisted N 2 extrusion process are not Scheme37.…”
Section: Oxidant-free Oxidative Addition Of C-heteroatom Bonds To Au mentioning
confidence: 91%
“… Base‐assisted gold redox catalysis for the cross‐coupling reaction of aryl diazonium salts with (a) alkenes, (b) allenes, and (c) alkynes …”
Section: Oxidant‐free Approaches For Homogeneous Au‐catalyzed Cross‐cmentioning
confidence: 99%
“…In 2017, Shi reported the Lewis base-assisted diazonium activation as a strategy to access gold oxidation and build a Au(I)/Au(III) catalytic cycle for the intramolecular oxy-and aminoarylation of alkenes, the arylative ring expansion of alkenes, the oxy-and aminoarylation of allenes, and the propargyl ester rearrangement of alkynes. [78] Additionally, in 2018 the group of Dughera reported the gold-catalyzed Heck and Suzuki-Miyaura couplings using arenediazonium o-benzenedisulfonimides as electrophilic partners. [79] They proposed a Au(I)/Au(III) catalytic cycle that did not require the presence of external oxidants since the obenzenedisulfonimide anion was suggested to act as an electron transfer agent that promoted the oxidation to Au(III) intermediate species via a radical pathway.…”
Section: Coupling Partners With Dual Rolementioning
confidence: 99%
“…Crucial to the success of this transformation was the nucleophile‐assisted activation of aryldiazonium salts, which were then added to Au(I) to yield Au(III) intermediates. In 2017, Shi reported the Lewis base‐assisted diazonium activation as a strategy to access gold oxidation and build a Au(I)/Au(III) catalytic cycle for the intramolecular oxy‐ and aminoarylation of alkenes, the arylative ring expansion of alkenes, the oxy‐ and aminoarylation of allenes, and the propargyl ester rearrangement of alkynes [78] . Additionally, in 2018 the group of Dughera reported the gold‐catalyzed Heck and Suzuki‐Miyaura couplings using arenediazonium o ‐benzenedisulfonimides as electrophilic partners [79] .…”
Section: Oxidant‐free Au(i)/au(iii) Cross‐coupling Catalysismentioning
confidence: 99%